A Contemporary View on Carnot’s Réflexions - Meyn, Jan-Peter (Entropy, 2024)
Entropy and energy had not yet been introduced to physics by the time Carnot wrote his seminal Réflexions. Scholars continue to discuss what he really had in mind and what misconceptions he might have had. Actually, his work can be read as a correct introduction to the physics of heat engines when the term calorique is replaced by entropy and entropy is used as the other fundamental thermal quantity besides temperature. Carnot’s concepts of falling entropy as an analogy to the waterfall, and the separation of real thermal processes into reversible and irreversible processes are adopted. Some details of Carnot’s treatise are ignored, but the principal ideas are quoted and assumed without modification. With only two thermal quantities, temperature and entropy, modern heat engines can be explained in detail. Only after the principal function of heat engines is developed is energy introduced as physical quantity in order to compare thermal engines with mechanical and electrical engines and, specifically, to calculate efficienc
Keywords: Carnot cycle; waterfall analogy; heat engine; combustion engine; diffusion; waste heat; gas turbine; efficiency

A new teaching concept on quantum physics in secondary schools - Bitzenbauer, Philipp; Meyn, Jan-Peter (Physics Education, 2020)
In this article, an approach to integrate contemporary quantum physics into secondary school teaching is presented. The Erlanger concept on quantum optics provides an experimental-based guideway to aspects of modern quantum physics. We avoid the traditional historical approach in order to overcome the lack of modern concepts of quantum physics. In an acceptance survey, initial empirical evidence for the acceptance of the developed explanatory approaches was evaluated.
Keywords: quantum optics; anticorrelation factor; single Photons; acceptance survey

An ultra-capacitor-based current source for magnetic field demonstration - Meyn, Jan-Peter (European Journal of Physics, 2010)
An ultra-capacitor in parallel with the output of a dc power supply reduces the source resistance and yields an electrical current of up to 900A through a low resistance load. The magnetic field of wires is made visible with iron filings over a large area. © 2010 IOP Publishing Ltd.
UnivIS-Import:2015-03-09:Pub.2010.nat.dphy.PI.PDP.anultr

A safe and effective modification of Thomson's jumping ring experiment - Waschke, Felix; Strunz, Andreas; Meyn, Jan-Peter (European Journal of Physics, 2012)
UnivIS-Import:2015-03-09:Pub.2012.nat.dphy.PI.PDP.asafea

Assessing Engineering Students’ Conceptual Understanding of Introductory Quantum Optics - Bitzenbauer, Philipp; Veith, Joaquin M.; Girnat, Boris; Meyn, Jan-Peter (Physics, 2022)
Quantum technologies have outgrown mere fundamental research in laboratories over recent years, and will facilitate more and more potentially disruptive applications in a wide range of fields in the future. In foresight, qualification opportunities need to be implemented in order to train qualified specialists, referred to as the future quantum workforce, in various fields. Universities world-wide have launched qualification programmes for engineers focusing on quantum optics and photonics. In many of these programmes, students attend courses on quantum physics contextualized via quantum optics experiments with heralded photons, because: (1) their experimental and physical foundations may be directly leveraged to teaching a number of quantum technology applications, and (2) physics education research has provided empirical evidence, according to which such quantum optics-based approaches are conducive to learning about quantum concepts. While many teachers are confident about the effectiveness of their concepts, there is little empirical evidence due to the lack of content-area-specific research tools. We present a 16-item concept inventory to assess students’ conceptual understanding of quantum optics concepts in the context of experiments with heralded photons adopted from a test instrument published in the literature. We have administered this Quantum Optics Concept Inventory as a post-test to N=216" role="presentation">N=216 students after instruction on quantum optics as part of an undergraduate engineering course. We evaluated the instruments’ psychometric quality, both in terms of classical test theory, and using a Rasch scaling approach. The Quantum Optics Concept Inventory enables a reliable measure (α=0.74" role="presentation">α=0.74), and the data gathered show a good fit to the Rasch model. The students’ scores suggest that fundamental quantum effects pose striking learning hurdles to the engineering students. In contrast, most of the students are able to cope with the experimental and technical foundations of quantum optics experiments with heralded photons and their underlying principles, such as the coincidence technique used for the preparation of single-photon states. These findings are in accordance with prior research, and hence, the Quantum Optics Concept Inventory may serve as a fruitful starting point for future empirical research with regard to the education of the future quantum workforce.
Keywords: quantum optics; concept inventory; Rasch scaling; quantum technology

Bestimmung der Planck-Konstanten h - Meyn, Jan-Peter (Praxis der Naturwissenschaften - Physik in der Schule, 2013)
UnivIS-Import:2015-03-09:Pub.2013.nat.dphy.PI.PDP.bestim

Colour mixing based on daylight - Meyn, Jan-Peter (European Journal of Physics, 2008)
Colour science is based on the sensation of monochromatic light. In contrast to that, surface colours are caused by reflection of wide sections of the daylight spectrum. Non-spectral colours like magenta and purple appear homologous to colours with spectral hue, if the approach of mixing monochromatic light is abandoned. It is shown that a large region of the colour space can be covered by mixing three primary colours derived from lossless spectral decomposition of daylight. These primaries are specified by hue, saturation and luminosity. Duality of additive and subtractive mixing is formulated quantitatively. Experimental demonstrations of calculated results are suggested. This paper is intended for undergraduate optics courses, and advanced interdisciplinary seminars on arts and physics. © 2008 IOP Publishing Ltd.
UnivIS-Import:2015-03-09:Pub.2008.nat.dphy.PI.PDP.colour

Demonstrating quantum random with single photons - Bronner, Patrick; Strunz, Andreas; Silberhorn, Christine; Meyn, Jan-Peter (European Journal of Physics, 2009)
We present an experiment for education which demonstrates random transmission or reflection of heralded single photons on beam splitters. With our set-up, we can realize different quantum random experiments by appropriate settings of polarization rotators. The concept of entanglement is motivated by correlated randomness. The experiments are suitable for undergraduate education and are available as interactive screen experiments. © 2009 IOP Publishing Ltd.
UnivIS-Import:2015-03-09:Pub.2009.nat.dphy.PI.PDP.demons

Demonstrating the Barkhausen effect with high signal-to-noise ratio - Meyn, Jan-Peter (European Journal of Physics, 2017)
Keywords: Barkhausen effect; amplifier; induction; demonstration; noise

Einführung in die Hydromechanik im fachübergreifenden Kontext - Meyn, Jan-Peter (PhyDid A, Physik und Didaktik in Schule und Hochschule [Elektronische Ressource], 2006)
UnivIS-Import:2015-03-09:Pub.2006.nat.dphy.PI.PDP.einfhr

Evaluation eines Unterrichtskonzepts zur Quantenoptik mit Einzelphotonenexperimenten – Ergebnisse einer Pilotstudie - Bitzenbauer, Philipp; Meyn, Jan-Peter (Naturwissenschaftliche Kompetenzen in der Gesellschaft von morgen, 2020)

Experimentelle Quantenphysik im Physikunterricht - Strunz, Andreas; Meyn, Jan-Peter (Praxis der Naturwissenschaften - Physik in der Schule, 2015)
Wir demonstrieren die Quantennatur des Lichts mit einer neu entwickelten Apparatur im Klassenzimmer. Einzelphotonenzustände werden mit einer Koinzidenzmethode präpariert. Die Auswertung von Signalen zweier Detektoren hinter einem halbdurchlässigen Spiegel ergibt eine Antikorrelation, die als Reflexion oder Tranmission einer unteilbaren Lichtportion interpretiert wird. Dass es sich dabei nicht um mechanistisch gedachte Teilchen handeln kann, ergibt die anschließende Interferenz in einem Michelson-Interferometer. Experimentelle Methoden und Begriffe entsprechen dem aktuellen Stand der Physik.

Experimente skalieren - Meyn, Jan-Peter (Praxis der Naturwissenschaften - Physik in der Schule, 2014)
UnivIS-Import:2015-04-02:Pub.2014.nat.dphy.PI.PDP.experi

Experimente skalieren - Meyn, Jan-Peter (PLUS LUCIS, 2015)

Förderung eines funktionalen Modellverständnisses Lernender in der Quantenphysik - Bitzenbauer, Philipp; Meyn, Jan-Peter (Naturwissenschaftlicher Unterricht und Lehrerbildung im Umbruch? Gesellschaft für Didaktik der Chemie und Physik Jahrestagung 2020, 2021)

Fostering experimental competences of prospective physics teachers - Bitzenbauer, Philipp; Meyn, Jan-Peter (Physics Education, 2021)
Physics teachers are often faced with the challenge of having to set up difficult experiments, or they have to consciously manipulate parameters in order to be able to demonstrate a phenomenon convincingly. Comprehensive laboratory courses are standard procedure in any study program for prospective physics teachers. However, many students, even after completing standard laboratory courses, show difficulties in standard experimental situations, such as measuring an electric current. We report on a new seminar concept for students in physics teacher study programs. This concept is based on the current state of research in physics education, on the teachers' professional competences, and on the modelling of experimental competence, justifying its embedding in teacher training. We present first results of a pilot study carried out to evaluate the seminar.<br
Keywords: experimental competence; teacher education; professional knowledge; assessment

Fostering students' conceptions about the quantum world - results of an interview study - Bitzenbauer, Philipp; Meyn, Jan-Peter (Progress in Science Education, 2021)
Background: Quantum physics is both a highly topical and challenging topic of physics education. Learning quantum physics is inherently difficult because it is unimaginative, counterintuitive and fundamentally different from what learners know from their everyday life and classical physics. The results of recent studies underline that students are often not aware of the relevance of quantum physics and its technologies for their own lives, which makes studying quantum physics even more difficult. This is the starting point of this article: With the Erlanger teaching concept, we present an introductory teaching concept for quantum physics at secondary schools with the aim, among others, to raise students’ awareness of the importance of modern quantum technologies today and in the future. Purpose: In order to evaluate which conceptions about the quantum world arise among students who are introduced to quantum physics with the Erlanger concept, we conducted an interview study. Sample/Setting: A random sample of N = 25 students was interviewed after the intervention (15 male, 10 female) in order to answer the questions mentioned above. The interviews had a duration of 25 – 40 minutes. Prior to the intervention, none of the students had any classroom instruction in quantum physics. Design and Methods: The students’ answers were transcribed and then evaluated on the basis of deductive and inductive categories using qualitative content analysis. The coding was done by independent coders (κ=0.84,95% - CI [0.68;1.00]). Additionally, a cluster analysis was performed and a three-cluster solution was extracted. The three clusters could be interpreted in terms of content and thus facilitate the characterization of occurring types of students’ conceptions after the intervention. Results: After the intervention with our concept, we found elaborated conceptions about the quantum world with the majority of respondents. 11 of the 25 students (cluster 1, labelled Primarily elaborate conception) are aware of the striking differences between quantum and classical physics, as all students in this cluster characterize the quantum world via effects or aspects that do not exist in classical physics. The importance of quantum physics for future technologies was named by the students combined in the cluster 2, labelled Quantum world as the world of technology. 10 of the students interviewed (cluster 3, labelled Quantum world as a classical world on a small scale) seem to stick to their pre-conceptions dominated by classical ways of thinking. Conclusions: Our article provides implications for both classroom practice and future research. For classroom practice, the Erlanger teaching concept serves as a proposal to bridge the gap between quantum physics and the everyday life of the learners. In addition, the results of the interview study presented in this paper make a contribution to the empirical research on students’ conceptions about quantum physics. We not only find individual, independent conceptions of learners, but we also show that there are dependencies between them, allowing us to extract types of conceptions. The extraction of such types of student conceptions for various further concepts of quantum physics will be part of future research and could contribute to our understanding of learning processes in quantum physics. Keywords: quantum physics, interview study, cluster analysis, teaching concept</e
Keywords: quantum physics; teaching concept

Gibt es die mechanische Analogie zum Schwingkreis? - Meyn, Jan-Peter (Stolpersteine überwinden im Physikunterricht - Anregung zu fachgerechten Elementarisierungen, 2018)
Keywords: Schwingkreis

Grundlegende Experimentiertechnik im Physikunterricht - Meyn, Jan-Peter (Oldenbourg, 2011)

Grundlegende Experimentiertechnik im Physikunterricht - Meyn, Jan-Peter (Oldenbourg Wissenschaftsverlag, 2013)
UnivIS-Import:2015-04-02:Pub.2011.nat.dphy.PI.PDP.grundl

Inhaltsvalidität eines Testinstruments zur Erfassung deklarativen Wissens zur Quantenoptik - Bitzenbauer, Philipp; Meyn, Jan-Peter (Didaktik der Physik - Beiträge zur DPG-Frühjahrstagung, 2020)
In der empirischen Unterrichtsforschung wird im Kontext von Testentwicklung oft von der Validierung eines Testinstruments gesprochen. Die Debatte über das Testgütekriterium Validität führte zu einer Verschiebung der Auffassung von Validität. Heute ist weniger von der Validität als Eigenschaft eines Tests die Rede. Vielmehr steht eine valide Testwertinterpretation im Zentrum der Sicherung von Testqualität. Dass ein Testverfahren valide Testwertinterpretation erlaubt, muss argumentativ abgeleitet werden. Die erforderlichen Argumentationsstränge sind dabei nicht standardisierbar. Insbesondere für Forschungsbereiche, in denen es nur wenig belastbare theoretische Vorarbeiten gibt, birgt das Hürden. Hier setzt dieser Artikel an: anhand eines „best-practice“-Beispiels aus der Didaktik der Quantenphysik wird aufgezeigt, wie ein solcher argumentativer Prozess methodisch erfolgen kann. Zunächst wird der Bedarf einer Neuentwicklung eines Testinstruments für die summative Evaluation eines Unterrichtskonzepts zur Quantenoptik begründet. Die Testentwicklung wird beschrieben. Inwiefern eine valide Testwertinterpretation möglich ist, wird argumentativ abgeleitet: Die Ergebnisse von einer Studie zum Lauten Denkens, sowie einer Expertenbefragung werden mit Ergebnissen einer quantitativen Pilotstudie kombiniert.

Interactive screen experiments with single photons - Bronner, Patrick; Strunz, Andreas; Silberhorn, Christine; Meyn, Jan-Peter (European Journal of Physics, 2009)
Single photons are used for fundamental quantum physics experiments as well as for applications. Originally being a topic of advance courses, such experiments are increasingly a subject of undergraduate courses. We provide interactive screen experiments (ISE) for supporting the work in a real laboratory, and for students who do not have access to a quantum optics laboratory. The main focus of the ISE is on undergraduate education, but some of the experiments are suitable for other levels of higher education as well. © 2009 IOP Publishing Lt
UnivIS-Import:2015-03-09:Pub.2009.nat.dphy.PI.PDP.intera

Labortische mit Gewinderaster: Modernes Experimentieren nicht nur in der Optik - Meyn, Jan-Peter (Praxis der Naturwissenschaften - Physik in der Schule, 2011)
UnivIS-Import:2015-03-09:Pub.2011.nat.dphy.PI.PDP.labort

Modellexperimente zur Quantenkryptographie - Schneider, Jörn; Meyn, Jan-Peter (Praxis der Naturwissenschaften - Physik in der Schule, 2016)

Musician's and Physicist's View on Tuning Keyboard Instruments - Lubenow, Martin; Meyn, Jan-Peter (European Journal of Physics, 2007)
The simultaneous sound of several voices or instruments requires proper tuning to achieve consonance for certain intervals and chords. Most instruments allow enough frequency variation to enable pure tuning while being played. Keyboard instruments such as organ and piano have given frequencies for individual notes and the tuning must be based on a compromise. The equal temperament is not the only solution, but a special choice. Unequal temperaments produce better results in many cases, because important major thirds and triads are improved. Equal temperament was not propagated by Johann Sebastian Bach, as is often stated in introductory literature on this topic. © 2007 IOP Publishing Ltd.
UnivIS-Import:2015-03-09:Pub.2007.nat.dphy.PI.PDP.musici

Observation of planetary motion using a digital camera - Meyn, Jan-Peter (Physics Education, 2008)
A digital SLR camera with a standard lens (50 mm focal length, f/1.4) on a fixed tripod is used to obtain photographs of the sky which contain stars up to 8m apparent magnitude. The angle of view is large enough to ensure visual identification of the photograph with a large sky region in a stellar map. The resolution is sufficient to observe the motion of Saturn, and of the satellites of Jupiter, within 24 h. © 2008 IOP Publishing Lt
UnivIS-Import:2015-03-09:Pub.2008.nat.dphy.PI.PDP.observ

Photonik macht Schule - Ein Schülerlabor zur modernen Optik und Quantenoptik - Vetter, Andreas; Strunz, Andreas; Bronner, Patrick; Meyn, Jan-Peter (Praxis der Naturwissenschaften - Physik in der Schule, 2010)
UnivIS-Import:2015-03-09:Pub.2010.nat.dphy.PI.PDP.photon

Physiker fährt Elektroauto - Meyn, Jan-Peter (Praxis der Naturwissenschaften - Physik in der Schule, 2015)

Primärfarben in Kunst und Physik - Meyn, Jan-Peter (Praxis der Naturwissenschaften - Physik in der Schule, 2013)
UnivIS-Import:2015-03-09:Pub.2013.nat.dphy.PI.PDP.primrf

Quantenphysik g²reifbar unterrichten - Bitzenbauer, Philipp; Meyn, Jan-Peter (PLUS LUCIS, 2019)

Quantenphysik = Quantenphysik? Assoziationen Forschender zur Quantenphysik - Winkler, Bianca; Bitzenbauer, Philipp; Meyn, Jan-Peter (Naturwissenschaftlicher Unterricht und Lehrerbildung im Umbruch? Gesellschaft für Didaktik der Chemie und Physik Jahrestagung 2020, 2021)

Quantitative analysis of a wind energy conversion model - Zucker, Florian; Strunz, Andreas; Gräbner, Anna; Meyn, Jan-Peter (European Journal of Physics, 2015)
A rotor of 12 cm diameter is attached to a precision electric motor, used as a generator, to make a model wind turbine. Output power of the generator is measured in a wind tunnel with up to 15 m s-1 air velocity. The maximum power is 3.4 W, the power conversion factor from kinetic to electric energy is cp = 0.15. The v3 power law is confirmed. The model illustrates several technically important features of industrial wind turbines quantitatively.
UnivIS-Import:2015-04-14:Pub.2015.nat.dphy.PI.PDP.quanti
Keywords: Betz factor; demonstration experiment; model; renewable energy; wind energy; wind turbine

Quantum physics ≠ quantum physics. A survey of researchers' associations - Winkler, Bianca; Bitzenbauer, Philipp; Meyn, Jan-Peter (Physics Education, 2021)
No consensus has been reached so far concerning the key topics on quantum physics suitable for secondary school teaching, despite comprehensive research. We identified the the variety of associations with quantum physics among professionals as a potential cause. From an explorative mind map study with N = 29 physics researchers, we derive six subject-specific focal points in the associations that researchers have with quantum physics.<br

Regenerative Energiequellen aus thermodynamischer Sicht - Meyn, Jan-Peter (Beiträge zur Experimentalphysik, Didaktik und computergestützten Physik, 2007)
UnivIS-Import:2015-04-20:Pub.2007.nat.dphy.PI.PDP.energi

Renewable energy sources in terms of entrophy - Meyn, Jan-Peter (European Journal of Physics, 2011)
UnivIS-Import:2015-03-09:Pub.2011.nat.dphy.PI.PDP.renewa

The kinematic advantage of electric cars - Meyn, Jan-Peter (European Journal of Physics, 2015)
UnivIS-Import:2015-10-26:Pub.2015.nat.dphy.PI.PDP.thekin

Toward Types of Students’ Conceptions About Photons: Results of an Interview Study - Bitzenbauer, Philipp; Meyn, Jan-Peter (Physics Teacher Education, 2022)
We report an exploratory interview study into students’ conceptions of photons developed by learners introduced to a QED model of photons as part of an introductory course in quantum physics at the secondary school level. By combining qualitative and quantitative research methods, we extract types of students’ imaginations about photons. Furthermore, we show that teaching a QED model of the photon might help to circumvent known (naive) particle notions of the photo

Über das Verschwinden der Reibung in der Mechanik - Meyn, Jan-Peter (Praxis der Naturwissenschaften - Physik in der Schule, 2008)
UnivIS-Import:2015-03-09:Pub.2008.nat.dphy.PI.PDP.berdas

"Und er würfelt doch!" - Optische Experimente zum Quantenzufall - Bronner, Patrick; Strunz, Andreas; Silberhorn, Christine; Meyn, Jan-Peter (Praxis der Naturwissenschaften - Physik in der Schule, 2013)
UnivIS-Import:2015-03-09:Pub.2013.nat.dphy.PI.PDP.underw

Von Koinzidenzen zu Wesenszügen der Quantenphysik: Erste Ergebnisse einer summativen Evaluation des Erlanger Unterrichtskonzepts zur Quantenoptik - Bitzenbauer, Philipp; Meyn, Jan-Peter (Didaktik der Physik - Beiträge zur DPG-Frühjahrstagung, 2020)
Mit dem Erlanger Unterrichtskonzept zur Quantenoptik wird das Ziel verfolgt, eine moderne Sichtweise auf die Quantenphysik zu vermitteln. Lernende sollen anschlussfähiges Wissen bis hin zu den Wesenszügen der Quantenphysik aufbauen. Im Rahmen einer summativen Evaluation mit Schülerinnen und Schülern der gymnasialen Oberstufe wird das Konzept evaluiert. Ein mixed-methods-Ansatz wurde gewählt, um verschiedene Perspektiven auf die Lernprozesse nachzeichnen zu können. Erste Ergebnisse aus einem Fragebogen zum deklarativen Wissen in Quantenoptik im Prä-Post-Follow-Up-Testdesign sowie einem Vorstellungsfragebogen zur Quantenphysik werden vorgestellt. Es zeigt sich: Lernende gelangen zu einem angemessenen Begriffsverständnis zur Quantenoptik und bauen ein überwiegend adäquates Verständnis der Wesenszüge auf, aber eine Teilchenvorstellung von Photonen scheint stabil zu sein.

Von Schnee- und Elektronenlawinen: Entwicklung eines Erklärvideos zu Einzelphotonendetektoren - Donhauser, Anna; Bitzenbauer, Philipp; Meyn, Jan-Peter (Didaktik der Physik - Beiträge zur DPG-Frühjahrstagung, 2020)
Analogiebildung ist ein methodisches Werkzeug zur Förderung naturwissenschaftlicher Lernprozesse. Für das Erlanger Unterrichtskonzept zur Quantenoptik wurde zur Vermittlung des Lernbereichs Einzelphotonendetektoren eine Analogie erarbeitet. Die Funktionsweise der Einzelphotonendetektoren wird dabei mit dem Entstehen und Abgehen von Schneelawinen verglichen. Mittels eines für die Vermittlung dieser Analogie konzipierten Erklärvideos werden die Schülerinnen und Schüler im Rahmen einer Unterrichtssequenz schrittweise durch die funktionalen Zusammenhänge und Entsprechungen geführt. Die Akzeptanz der Analogie als Lernhilfe wurde in Akzeptanzbefragungen mit Schülerinnen und Schülern der gymnasialen Oberstufe evaluiert.
Keywords: Erklärvideo; Quantenphysik; Analogie; Didaktische Rekonstruktion

Wärme und Energie - Meyn, Jan-Peter (De Gruyter Oldenbourg, 2020)
Keywords: Physik; Thermodynamik; statistische Physik

Zur Geschichte des Photons - Meyn, Jan-Peter (Praxis der Naturwissenschaften - Physik in der Schule, 2013)
UnivIS-Import:2015-03-09:Pub.2013.nat.dphy.PI.PDP.zurges